'The pilot's periplus': Ezra Pound, Cyril Connolly, and the Forms of Late Modernist Travel. Issue 2 (July 2017) - Williams, Annabel
Abstract : This article argues that unexamined connections between Ezra Pound and Cyril Connolly illuminate a remodelling of form in late modernist travel writing, in a period when the genre was threatened by wartime restrictions on movement. In Cyril Connolly's The Unquiet Grave (1944) and Ezra Pound's The Pisan Cantos (1948), the 'intellectual voyage' becomes a compensatory response to the authors' enforced stasis during the Second World War, and to their separation from those places in Europe whose influence was integral to their aesthetic sensibilities. Both writers adapt some of the formal strategies of high modernism to respond to this. The resulting late modernist form might be thought of as a 'periplus': like the navigational chart, it is shaped by a subjective 'pilot's perspective', and in communicating the writers' journeys it relies on the affective quality of movement. In both works, structural and figurative motifs of the waveform in states of flux and recession reflect the writers' compromising positions between nostalgia or escapism, and innovation.